Graham-Little-Piccardi-Lassueur Syndrome: Two Case Reports - Piya, Smriti; Bhusal, Mohan; Pathak Thapa, Deeptara; Shrestha, Joshana (Nepal Journal of Dermatology, Venereology & Leprology, 2024)
Graham-Little-Piccardi-Lassueur Syndrome (GLPLS) is a rare lichen planopilaris (LPP) subtype associated with scarring alopecia. It is thought to be an immune-mediated cause of alopecia. It is characterized by a triad of multifocal cicatricial alopecia of the scalp, noncicatricial alopecia of the axilla, and groin and a follicular lichen planus (LP) eruption. Herein, we present 2 cases of GLPLS. The first case is of a 33-year-old female presented with classical lichen planopilaris (LPP) of the scalp, follicular hyperkeratosis of bilateral arms, and noncicatricial alopecia of armpits. In the second case, a 17-year-old female presents with frontal fibrosing alopecia (FFA) of the scalp, follicular hyperkeratotic papules of the scalp, and noncicatricial alopecia of the bilateral armpits and genitalia. The physician can miss GLPLS due to the rarity of the condition.